1997
DOI: 10.1177/000765039703600406
|View full text |Cite
|
Sign up to set email alerts
|

The Corporate Social-Financial Performance Relationship

Abstract: This research note analyzes the relationship between indicators of corporate social and financial performance within a comprehensive theoretical framework. The results, based on data for 67 large U.S. corporations for 1982-1992, reveal no significant negative social-financial performance relationships and strong positive correlations in both contemporaneous and lead-lag formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
840
5
54

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,146 publications
(949 citation statements)
references
References 10 publications
50
840
5
54
Order By: Relevance
“…The most widely accepted theoretical framework treating the existence and nature of the relationship between CSR and firm performance is to be found in the work of Preston and O'Bannon (1997). They establish six possible relationships between the two variables.…”
Section: Theorical Frameworkmentioning
confidence: 99%
“…The most widely accepted theoretical framework treating the existence and nature of the relationship between CSR and firm performance is to be found in the work of Preston and O'Bannon (1997). They establish six possible relationships between the two variables.…”
Section: Theorical Frameworkmentioning
confidence: 99%
“…Enterprises with high social performance have good social image, thereby stakeholders will take concrete action to support, and thus enhance the company's financial performance. It is namely social impact hypothesis, scholars support this hypothesis [15]. Numbers of operational variables have significant impact on financial performance and social performance in Table I listed above.…”
Section: E Hypotheses Hypothesis Established In This Study Is: Therementioning
confidence: 78%
“…The authors suggested that attempts to reduce implicit costs of socially irresponsible actions would lead to an increase in explicit costs. Preston and O'Bannon (1997) provided a "social impact hypothesis" that links the ability to know the expectations of various stakeholders to a positive impact on financial performance. The positive relation may be justified with the assumption that costs incurred for CSP programs are only minimally comparable to potential benefits.…”
Section: The Relationship Between Csp-cfpmentioning
confidence: 99%